Sustainable Development Practices; a Descriptive Approach to Small Enterprises from Guadalajara, Mexico - Navarrete Baez, Francisco E. (Cuadernos de Administración, 2015)
A descriptive study exposes the practices currently conducted by small and mid-sized enterprises (SME) from the metropolitan zone of Guadalajara, Mexico, regarding corporate sustainable development. Nearly 400 companies were found. A questionnaire was taken as reference, previously elaborated and validated, with over 100 questions on corporate practices of sustainable development, applied to the company´s owner. The results were divided into five categories. The data were captured and analyzed based on a descriptive statistics orientation. The results describe their current situation, finding that over 50% of the SMEs from the metropolitan zone of Guadalajara are below these practices, which are not part of their objectives, besides a decoupling existing with all their stakeholders. In the end, some suggestions are made on how to guide SMEs to increase their degree of commitment in this theme